Development of Small Halal Food Processing Enterprises in Three Southern Border Provinces to Enhance Food Safety - Sukjuntra, Jariya; Kanpairo, Kamontip; Srisuk , Suteera; Na-Nakorn, Kuenchan (Area Based Development Research Journal, 2020)
The development of food production facilities following good food production methods is the basis of food safety management that an entrepreneur needs to build up consumer confidence. The objectives of this project are generating knowledge, understanding the academically correct principles, and developing food production facilities by the standards. The project has involved ten halal food processing enterprises from the provinces of Pattani (4), Yala (4), and Narathiwat (2), producing two types of halal food: ready-to-eat food (fresh rice noodles, rice crackers) and convenience food (Luk-Yee products, Hin banana chips, fish crackers, ginger powder, chilli paste, Nam-Wa banana sticks, and toasted coconut). The research methods are as follows: 1) entrepreneur selection 2) enterprise assessment before project participation, 3) site visit, 4) food processing facility development and 5) enterprise assessment after the operation. The research results show that enterprise assessment scores in all categories meet the standards, and their food products have accredited quality certification with a four-star level (5 enterprises) and five-star level (2 enterprises) from the best of One Tambon One Product (OTOP) selection of the Department of Community Development in 2019. In conclusion, this can ensure that a safety arrangement in the production of all participating food enterprises achieves the standards with potentialities for product development, shelf life research and marketing strategy.